Training and Mentoring of Probiotic Milk Fermentation Technology Development in Purwodadi Village, Purwodadi Sub-District, Pasuruan - Achmad Toto Poernomo; Asri Darmawati; Isnaeni Isnaeni; Sudjarwo Sudjarwo (LP2M Universitas Jember, 2021)
Purwodadi sub-district has a surplus of dairy milk with a production of 25 tons of milk per day per KUD. There are 4 milk industry in Purwodadi sub-district as suppliers of PT Nestle. The problem is, dairy products are not entirely absorbed by the market, so it is necessary to look for breakthroughs in the distribution of dairy products that have an average price of IDR 8,000-13,000 per liter. Diversification of milk into fermented milk products will increase prices by five times, so that it is expected to increase people's income, because not only is the product variant increasing, but the market is also increasing. The result of the training shows that all participants experience a significant increase in knowledge, indicated by higher post-test result compared to the pre-test result. Another result known is that this probiotic-fermented milk can be used as a medium for a source of economic improvement for the family. This is proven when yogurt made by the community of Purwodadi has been sold among them as an additional drink during community meetings. Apart from that, this training will create a climate that enables the potential of the Youth Organization (Karang Taruna) and Family Welfare Program (PKK) to develop, namely to build group creative power by encouraging, motivating, and raising awareness of the potential of the village and efforts to develop it.